PENGGUNAAN METODE KOMPUTERISASI DALAM PENENTUAN TAHANAN KAPAL TANKER - Erik Sugianto; Hendika Puji Haditama (ROTOR, 2017)
The ship resistance is influential to choose the ship's main engine, especially tankers that have large block coefficients. In general, ship resistance was obtained by modeling the vessel on a certain scale and then testing on the experimental tank. However, this test requires high funding, because testing requires special places such as towing tanks that have expensive operating costs. This research is intended to get ship prisoner with computerized method for tanker ship. Then the result is validated by Holtrop mathematical approximation method. The result of computerized method for speed 11.4 knots got the value of ship resistance is 86.2 KN. While the method of mathematical approach generated ship resistance is 74.38 KN. So the ship's resistance used to determine the tanker machine is 86.2 KN. Keywords: Ship resistance, tanker, computerized